Natural Dibenzo[b,f]oxepines, Pacharin and Bauhiniastatin-1, Isolated from Bauhinia acuruana Induce Apoptosis on Breast Cancer Cells via MCL-1 Protein Reduction - Souza, Silvia de Maria; Souza, Luciano Santos de; Silva, Valdenizia Rodrigues; Soares, Milena Botelho Pereira; Bezerra, Daniel Pereira; Gois, Roberto Wagner da Silva; Silva, Horlando Carlota da; Santiago, Gilvandete Maria Pinheiro; Militao, Gardenia Carmen Gadelha (Planta Medica, 2022)
Herein, we describe the antiproliferative effects of two natural dibenzo [b,f]oxepines, pacharin and bauhiniastatin-1, isolated from Bauhinia acuruana on a breast cancer cell line and the mode of action underlying the cytotoxicity. Both compounds were cytotoxic in a panel of six tumor lines analyzed by the MTT assay, and IC50 values ranged from 7.8 to 45.1 µM, including human breast adenocarcinoma (MCF-7) cells. In contrast, none of the compounds were cytotoxic on normal human peripheral blood mononuclear cells (IC50 > 100 µM). Human breast adenocarcinoma (MCF-7) cells treated with pacharin or bauhiniastatin-1 20 µM for 24 h presented a reduction in cell volume and intensification of chromatin condensation, DNA fragmentation, and apoptotic cells. These findings became more evident after 48 h of exposure. Antiapoptotic B-cell lymphoma-2 family members, such as myeloid cell leukemia-1 and B-cell lymphoma-extra large, are important targets in cancer cells since their overexpression confers resistance to cancer treatments. A significant reduction of the myeloid cell leukemia-1 protein levels in human breast adenocarcinoma (MCF-7) cells after 24 h of treatment with pacharin or bauhiniastatin-1 at 20 µM was observed, while the B-cell lymphoma-extra large protein content was reduced in bauhiniastatin-1-treated cells at 40 µM only. The cytotoxic effects of pacharin and bauhiniastatin-1 are likely linked to myeloid cell leukemia-1 inhibition, which leads to the apoptosis of breast adenocarcinoma cells.
Keywords: Bauhinia acuruana; Fabaceae; pacharin; bauhiniastatin-1; breast adenocarcinoma; MCL-1; Bcl-xL; apoptosis